Highly enhanced energy storage properties of H2O2-hydroxylated rare earth ferrites (LaFeO3 and GdFeO3) nanofillers in poly(vinylidene fluoride)-based nanocomposite films - Singh V.P.; Singh C.B.; Satyarthi S.K.; Kumar D.; Singh A.K. (My University, 2025)
Pure PVDF has higher breakdown strength but low dielectric and ferroelectric properties. Thus, we synthesized the LaFeO3 and GdFeO3 nanoparticles with the help of solid-state method. The H2O2-hydroxylated LaFeO3 (Hy-LFO) and GdFeO3 (Hy-GdFO) nanoparticles were used for the first time as filler in the PVDF to get nanocomposite films with improved dielectric and ferroelectric properties. The solution cast method has been used for the preparation of the nanocomposite films. The H2O2 hydroxylation improved the interfacial interaction between the filler and the PVDF matrix. X-ray diffraction and Fourier transform infrared spectroscopy spectra analyses confirmed the formation of polar phases (β, γ-phases) of PVDF in dominance with nonpolar phase (α-phase) after nanocomposite formation. Differential scanning calorimetry measurements reveal that the peak corresponding to the α-phase of PVDF is fully diminished in the nanocomposite films. The increment in polar phase fraction in developed nanocomposite films results from the interfacial interaction due to nanofiller. The ferroelectric hysteresis loop recorded for the PVDF/Hy-LFO and PVDF/Hy-GdFO nanocomposite films reveals relatively improved polarization as compared to pure PVDF. The developed nanocomposites can be suitable candidate for energy storage applications. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.